Increased body mass in infancy and early toddlerhood in Angelman syndrome patients with uniparental disomy and imprinting center defects. (17th November 2014) - Brennan, Marie‐Luise; Adam, Margaret P.; Seaver, Laurie H.; Myers, Angela; Schelley, Susan; Zadeh, Neda; Hudgins, Louanne; Bernstein, Jonathan A.
<x xml:space="preserve">Abstract</x> The diagnosis of Angelman syndrome (AS) is based on clinical features and genetic testing. Developmental delay, severe speech impairment, ataxia, atypical behavior and microcephaly by two years of age are typical. Feeding difficulties in young infants and obesity in late childhood can also be seen. The NIH Angelman‐Rett‐Prader‐Willi Consortium and others have documented genotype–phenotype associations including an increased body mass index in children with uniparental disomy (UPD) or imprinting center (IC) defects. We recently encountered four cases of infantile obesity in non‐deletion AS cases, and therefore examined body mass measures in a cohort of non‐deletion AS cases. We report on 16 infants and toddlers (ages 6 to 44 months; 6 female, and 10 male) with severe developmental delay. Birth weights were appropriate for gestational age in most cases, >97th% in one case and not available in four cases. The molecular subclass case distribution consisted of: UPD (n = 2), IC defect (n = 3), UPD or IC defect (n = 3), and UBE3A mutation (n = 8). Almost all (7 out of 8) UPD, IC and UPD/IC cases went on to exhibit >90th% age‐ and gender‐appropriate weight for height or BMI within the first 44 months. In contrast, no UBE3A mutation cases exhibited obesity or pre‐obesity measures (percentiles ranged from <3% to 55%). These findings demonstrate that increased body mass may be evident as early as the first year of life and highlight the utility of considering the diagnosis of AS in the obese infant or toddler with developmental delay, especially when severe. Although a mechanism explaining the association of UPD, and IC defects with obesity has not been identified, recognition of this correlation may inform investigation of imprinting at the PWS/AS locus and obesity. © 2014 Wiley Periodicals, Inc.